13C Urea Breath Test for Helicobacter pylori: Evaluation of 10-minute Breath Collection - Marina Mauro; Vladimir Radovic; Melanie Wolfe; Markad Kamath; Premsyl Bercik; David Armstrong (Canadian Journal of Gastroenterology)
AIM: To determine whether a shortened 13C urea breath test (13C UBT) (breath collection time of 10 min) is as reliable as the standard assay (30 min).